Using Internet of Things Techniques to Measure Parameters of Oil Tanks - Abbod, Ali A.; Zwyer, Nour Basim (Journal of Petroleum Research and Studies, 2021)
Systems change currently response to the requirements of modern society where the emergence of a lot of sensors and controllers in all forms it led to the use of IoT that make things connect with Internet These technologies provide advanced functionality for enterprises and oil installations to transmit data in real time to avoid flood and fire situations in oil Tanks. The system consists of two stations: the tank station and the control station for monitoring and controlling the level and temperature of the products and the detection of fire. Where, the tank station is equipped with three sensors, which are level, temperature, fire sensors. The connection between the tank station and the control station is wireless connection by XBee. The control station is to display data to the user via graphical user interface that were programmed by Visual Basic.net and stored in a local database designed by SQL Server simultaneously sending data to the Think Speak so that authorized persons can access the data remotely. The system tested for several months proved during this period that it has the ability to address some problems such as floods and fires where it gives alerts before the problem occurs.